Media Psychology Approaches in Digitalization and Human Communication - Vimala, Govindaraju (IGI Global Information Science Reference (an imprint of IGI Global), 2023)
Digital communication between people is fundamentally changing the nature of communication. Recent technological advances have dramatically impacted the way people communicate. Technology has become an integral part of how people communicate with each other, increasingly replacing face-to-face communication. With the rapid development of technology, many people fear that people are getting too immersed in this digital world and not fully integrated into the real world. This chapter aims to provide an overview of media psychology theories and approaches in digitalization and human communication.